2023
DOI: 10.1007/s00737-023-01332-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations between maternal psychological distress and mother-infant bonding: a systematic review and meta-analysis

Abstract: Purpose Maternal psychological distress and mother-infant bonding problems each predict poorer offspring outcomes. They are also related to each other, yet the extensive literature reporting their association has not been meta-analysed. Methods We searched MEDLINE, PsycINFO, CINAHL, Embase, ProQuest DTG, and OATD for English-language peer-reviewed and grey literature reporting an association between mother-infant bonding, and multiple indicators of materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Parents reporting high‐level of infant carrying had fewer bonding impairments than parents reporting low levels of infant carrying. Parental bonding, the emotional connection from parent to child, has been shown to play an important role in postpartum mental health (Badr et al., 2018; Behrendt et al., 2016; Eitenmüller et al., 2022; Nakano et al., 2019; O'Dea et al., 2023) and to affect a child's socio‐emotional development (Fuchs et al., 2016; Joas & Möhler, 2021; Le Bas et al., 2022). The association between parental reflective functioning and parental bonding is in line with previous findings (Pazzagli et al., 2022) suggesting that parental reflective functioning may have an important (mediating) role in the developing parent‐infant bond.…”
Section: Discussionmentioning
confidence: 99%
“…Parents reporting high‐level of infant carrying had fewer bonding impairments than parents reporting low levels of infant carrying. Parental bonding, the emotional connection from parent to child, has been shown to play an important role in postpartum mental health (Badr et al., 2018; Behrendt et al., 2016; Eitenmüller et al., 2022; Nakano et al., 2019; O'Dea et al., 2023) and to affect a child's socio‐emotional development (Fuchs et al., 2016; Joas & Möhler, 2021; Le Bas et al., 2022). The association between parental reflective functioning and parental bonding is in line with previous findings (Pazzagli et al., 2022) suggesting that parental reflective functioning may have an important (mediating) role in the developing parent‐infant bond.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we had 99.99% power to observe large correlations of r = .50 and 89.95% power to observe medium correlations of r = .30, but only 17.89% power to observe small correlations of r = .10. Prior work examining links between maternalinfant bonding and maternal mental health suggests that effect sizes for our hypotheses would range from medium to large (O'Dea et al, 2023).…”
Section: Data Analysis Planmentioning
confidence: 99%
“…Although no research has explicitly tested potential mechanisms, there are many possible reasons for lower average maternal-infant bonding in mothers of twins. Higher levels of stress (Wenze et al, 2023), resulting from increased caregiving burden, time demands, sleep disruption, medical complications (Wenze et al, 2020), and the unique challenge of attempting to connect simultaneously with both babies (Bryan, 2003) could contribute; links between maternal parenting stress and poor maternal-infant bonding are well-established (Lutkiewicz et al, 2020;O'Dea et al, 2023). Parents of twins often express concern that the need to be highly task-focused interferes with opportunities to bond with their babies (Gowling et al, 2021;Holditch-Davis et al, 1999).…”
Section: Statement Of Relevance To Infant and Childhood Early Mental ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies revealed that substantial impairment of maternal bonding is evident in the presence of antenatal depression (Hildingsson & Rubertsson, 2022) and postpartum depression (PPD) (Lutkiewicz et al, 2020;Moehler et al, 2006). Three prior narrative reviews (Edwards et al, 2017;McNamara et al, 2019;Tichelman et al, 2019) reported that maternal depression and stress symptoms were associated with maternal bonding problems; additionally, one recent meta-analysis (O'Dea et al, 2023) concluded that maternal symptoms of depression and stress are associated with an increased risk of poorer mother-child bonding that will likely persist beyond the first year postpartum. As could be expected, the prevalence of maternal bonding problems in mothers with psychiatric disorders and depression is generally higher than in community samples (O'Higgins et al, 2013;Vengadavaradan et al, 2019).…”
mentioning
confidence: 99%